How neurons generate behaviour in a hatchling amphibian tadpole: an outline - Roberts, Alan; Li, Wen-Chang; Soffe, Stephen R. (Frontiers in Behavioral Neuroscience, 2010)
Adult nervous systems are so complex that understanding how they produce behaviour remains a real challenge. We chose to study hatchling Xenopus tadpoles where behaviour is controlled by a few thousand neurons but there is a very limited number of types of neuron. Young tadpoles can flex, swim away, adjust their trajectory, speed-up and slow-down, stop when they contact support and struggle when grasped. They are sensitive to touch, pressure, noxious stimuli, light intensity and water currents. Using whole-cell recording has led to rapid progress in understanding central networks controlling behaviour. Our methods are illustrated by an analysis of the flexion reflex to skin touch. We then define the 7 types of neuron that allow the tadpole to swim when the skin is touched and use paired recordings to investigate neuron properties, synaptic connections and activity patterns. Proposals on how the swim network operates are evaluated by experiment and network modelling. We then examine GABAergic inhibitory pathways that control swimming but also produce tonic inhibition to reduce responsiveness when the tadpole is at rest. Finally, we analyse the strong alternating struggling movements the tadpole makes when grasped. We show that the mechanisms for rhythm generation here are very different to those during swimming. Although much remains to be explained, study of this simple vertebrate has uncovered basic principles about the function and organisation of vertebrate nervous systems.